Analysis of the Impact of Infrastructure Development on Gross Regional Domestic Product of West Lombok Regency 2010 – 2023 - Faschal Syawkani Wahid; Muhammad Alwi; Muhammad Dzul Fadli (Indonesian Development Economics and Localities, 2025)
The Publisher, in agreement with the Editor-in-Chief, has retracted this article following a thorough evaluation. The initial investigation raised concerns identified across several articles, including this one. These concerns include, but are not limited to, issues with the peer review process, the inclusion of inappropriate or irrelevant references, the presence of nonstandard phrases, and content that falls outside the journal’s scope. In addition, the withdrawal of this article was requested by the corresponding author for personal reasons, and this request was fully endorsed by all co-authors. In light of these factors, the Publisher, in consultation with the Editor-in-Chief, has determined that the integrity of the article’s results and conclusions cannot be guaranteed. Accordingly, the article has been formally retracted.